Occurrence, spatial distribution and risk and hazard assessments of antibiotics in drinking water sources of a polluted large river basin in China. Issue 1 (2nd January 2018) - Ju, H.; Zhang, J.; Sun, C.
Abstract : The Yinma River basin is located in central Jilin Province, China and is the primary source for domestic water and farmland irrigation in the region. Water quality directly affects the ecosystem and public health. With the development of industrial and pharmaceutical plants, aquaculture, and animal husbandry, which are sources of antibiotic pollution, there is increasing discharge into the aquatic environment of the Yinma River basin. To the best of our understanding, there have been no studies on aquatic pollution by antibiotics in this region. Thus, this study investigated the concentration levels and spatial distribution of antibiotics in the water of the Yinma River basin, and evaluated the human health hazards and ecological risks norfloxacin, enrofloxacin, ciprofloxacin, sulfamethoxazole and metronidazole were analyzed in 17 water samples from 13 provincial monitoring sections and 4 state monitoring sections. The results showed that the mean concentration of metronidazole in water was the highest, at 85.21 ng l −1, while enrofloxacin was undetected in all of the samples, and therefore, had the lowest concentration. The total concentrations of the 5 antibiotics ranged from 52.63 ng l −1 to 234.98 ng l −1, with a mean value of 142.06 ng l −1 . Spatially, the highest total concentration was observed in the largest residential area, while the lowest total concentration was observed in the largest grassland. The results for hazard quotients suggested that the exposure of water to individual and complex antibiotics from all of the sampling sites posed little to no hazard to human health, but the drinking water pathway significantly contributed to human health hazards; the health hazards to men were higher than those to women. In the Yinma River basin, some sampling sites posed either low or medium risks to the aquatic ecosystem, which are indicated by the levels of individual and complex antibiotics.